2006
DOI: 10.1093/ajcn/84.5.1062
|View full text |Cite
|
Sign up to set email alerts
|

Dietary magnesium and fiber intakes and inflammatory and metabolic indicators in middle-aged subjects from a population-based cohort

Abstract: Reduced fiber intake was significantly associated with metabolic abnormalities; the magnesium effect might be confounded by fiber being in foods that also provided magnesium. Lower magnesium and fiber intakes were linked to hs-CRP >/= 3 mg/L in both the entire cohort and healthy persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 51 publications
6
93
1
1
Order By: Relevance
“…In large cohort studies, high fibre intakes have consistently been associated with a reduction in coronary heart disease risk (Pereira et al, 2004;Flight and Clifton, 2006). Cross-sectional (King et al, 2003;Ajani et al, 2004;King, 2005;Bo et al, 2006) and longitudinal (Ma et al, 2006) studies indicate an inverse association between dietary fibre (DF) intake and levels of inflammatory markers. In the prospective study by Ma et al (2006), multiple dietary and CRP measurements were taken and an inverse association between DF intake in both crosssectional and longitudinal analyses was found.…”
Section: Introductionmentioning
confidence: 99%
“…In large cohort studies, high fibre intakes have consistently been associated with a reduction in coronary heart disease risk (Pereira et al, 2004;Flight and Clifton, 2006). Cross-sectional (King et al, 2003;Ajani et al, 2004;King, 2005;Bo et al, 2006) and longitudinal (Ma et al, 2006) studies indicate an inverse association between dietary fibre (DF) intake and levels of inflammatory markers. In the prospective study by Ma et al (2006), multiple dietary and CRP measurements were taken and an inverse association between DF intake in both crosssectional and longitudinal analyses was found.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies included both men and women, and two studies consisted women only. Five studies used semi-quantitative food frequency questionnaires to collect dietary data, while other two studies used secondary dietary data from NHANES (1999-2000 and 1999-2002).In the original studies, dietary Mg intake was either categorized into three / four groups based on RDA levels (10,18) or divided into tertiles or quintiles (4,(13)(14)(15)17). Serum CRP was measured by using high sensitivity assay techniques (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A random effects meta-regression(16) was used to assess the overall linear relation between Mg intake and geometric mean levels of CRP with inverse variance as weights for each study. We also extracted ORs with 95% confidence intervals (CIs)in three cross-sectional studies (10,17,18). Natural logarithms transformed ORs and 95% CIs were used to compute the corresponding SEs.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Several studies have assessed relation of dietary magnesium with inflammatory markers [39][40][41][42][43][44] . In this study, higher inflammatory markers were observed among patients with magnesium intake lower than RDA.…”
Section: Discussionmentioning
confidence: 99%